Effect of Sidr (Beri) honey on reduction of post tonsillectomy pain in children: a randomised controlled trial. - Malik, Muhammad Omar (ADVANCES IN BASIC MEDICAL SCIENCES, 2019)
Introduction: The most important complaint reported following tonsillectomy is pain. Acetaminophen and non-steroidal anti-inflammatory drugs are mostly used for relieving pain. Honey is used for wound healing since ages. We compared the effectiveness of acetaminophen and acetaminophen plus honey in relieving post-tonsillectomy pain. Methods: It was a prospective, randomised controlled trial conducted in ENT department of CMH Kharian. 220 children undergoing tonsillectomy were randomised to either receiving acetaminophen or acetaminophen plus honey for 7-10 days. Visual analogue scale (VAS), Verbal rating scale (VRS) and Numerical rating scale (NRS) were used to record post-op pain. Age, pain scores on VAS and post-op day of pain relief were compared between the two groups by independent sample t test. Post operation pain relief was defined as pain less than 3 on VAS. Results: The participants were between 6-15 years with mean age of 9.9 ± 2.15 in honey group and 10.3 ± 2.28 in control group (p=0.181). On the day of operation pain was almost same in both the groups (6.85 ± 1.07 in honey vs 6.83 ± 1.08 in control). From first post operation day onwards pain was significantly less in honey group as compared to control (5.30±1.19, 5.83 ± 1.08, p= 0.001). Post-op pain relief was also earlier in the honey group (6.13±1.85 days) as compared to control (7.42 ± 1.13, p= <0.001). Conclusion: Following tonsillectomy in children, oral honey administration is helpful in relieving post-op pain. Honey administration should be started as soon as possible after tonsillectomy.